Let them eat chaos - Tempest, Kae, 1985- (Picador poetry., 2016)
"Let Them Eat Chaos, Kate Tempest's new long poem written for live performance and heard on the album release of the same name, is both a powerful sermon and a moving play for voices. Seven neighbours inhabit the same London street, but are all unknown to each other. The clock freezes in the small hours, and, one by one, we see directly into their lives: lives that are damaged, disenfranchised, lonely, broken, addicted. Then a great storm breaks over London, and brings them out into the night to face each other--and offers them a chance to connect. Tempest argues that our alienation from one another has bred a terrible indifference to our own fate, but she counters this with a plea to challenge the forces of greed which have conspired to divide us, and mend the broken home of our own planet while we still have time. Let Them Eat Chaos is a cri de coeur and a call to action, and, both on the page and in Tempest's electric performance, one of the most powerful poetic statements of the year"--Page 4 of cover.